Correction: Huang et al. Toxicity Assessment of 36 Herbicides to Green Algae: Effects of Mode of Action and Chemical Family. Agrochemicals 2024, 3, 164–180 - Jian Huang; Xiuying Piao; Yanming Zhou; Simeng Li (Agrochemicals)
Jian Huang, Xiuying Piao, and Yanming Zhou were not included as authors in the original publication [...]